Maori Television: The First Ten Years - Smith, Jo (Auckland University Press, 2016)
Established in 2004, Maori Television has had a major impact on the New Zealand broadcasting landscape. But over the past year or so, the politics of Maori Television have been brought to the foreground of public consciousness, with other media outlets tracking Maori Television's search for a new CEO, allegations of editorial intervention and arguments over news reporting approaches to Te Kohanga Reo National Trust.Based on a Marsden Grant and three years of interviews with key stakeholders – staff, the Board, other media, politicians, funders and viewers – this is a deep account of Maori Television in its first ten years. Jo Smith argues that today's arguments must be understood within a broader context shaped by non-Maori interests. Can a Maori broadcaster follow both tikanga and the Broadcasting Standards Authority? Is it simply telling the news in Maori, or broadcasting the news with a Maori perspective? How can it support te reo Maori at the same time as appeal to all New Zealand? How does it function as the voice of its Maori stakeholders?Offering five frameworks to address the challenges of a Maori organisation working within a wider non-Maori context, this is a solidly researched examination of Maori Television's unique contribution to the media cultures of Aotearoa New Zealand.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; Nouvelle-Zélande/Aotearoa (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."-- Provided by publisher.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Haerenga Wairua: Spirit(ual) Journeys in Twenty-First-Century Māori Cinema - Walker-Morrison, Deborah (Canadian Journal of Film Studies, 2020)
Haerenga Wairua / Spiritual Journeys explore le cinéma maori en tant que 4e cinéma, dans son articulation de la spiritualité maorie comme un ensemble de croyances et de pratiques vivantes et d’une grande pertinence pour ce XXIe siècle. Après une brève description des termes et croyances clés, l’auteure analyse deux longs-métrages de fiction récents, The Strength of Water (Armagan Ballantyne, scr Briar Grace-Smith, NZ & Allemagne 2009) et The Pā Boys (Himiona Grace, NZ, 2014) comme emblématiques des pratiques cinématographiques autochtones, en ce qu’ils mettent fortement en avant différents niveaux et expériences de transformation spirituelle, via divers voyages au propre comme au figuré : voyages réels, voyages psychologiques ET expériences après la mort, donc voyages spirituels. Positionnant ces films dans le contexte des traditions spirituelles de narration littéraire et cinématographique, l’auteure explore les diverses techniques filmiques et cinématographiques mises en œuvre pour rendre l’expérience spirituelle, via le son et l’image, en mettant en évidence les liens avec la Terre, l’Eau et l’environnement naturel en tant qu’éléments spirituels et souvent surnaturels. Alors que ces derniers sont généralement interprétés par les critiques et chercheurs allochtones comme étant de l’ordre du fantastique, dans le discours établi du réalisme magique, l’auteure avance plutôt que les représentations autochtones ne peuvent être ni expliquées ni contenues de manière adéquate par ce terme, et propose à sa place celui de « réalisme spirituel autochtone ». L’auteure conclut en soulignant la pertinence de voix autochtones comme celles-là, qui expriment une spiritualité enracinée dans l’interdépendance de tous êtres et de toutes choses : force de guérison dans notre planète meurtrie.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé